Method for hydrophobing cellulose nanofiber, and cellulose nanofiber hydrophobed body

By converting cellulose nanofiber hydroxyl groups into amide groups using carbonyl monomers and amines, the method addresses the limitations of TEMPO-based hydrophobization, achieving enhanced heat resistance and resin compatibility for broader industrial applications.

JP2025011911APending Publication Date: 2025-01-24RESONAC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023114327
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Conventional methods for hydrophobizing cellulose nanofibers using TEMPO result in the presence of halogen and ionic substances, leading to environmental and industrial disadvantages, and the hydrophobized cellulose nanofibers lack sufficient heat resistance for applications requiring high temperatures.

Method used

A method involving the use of carbonyl group-containing monomers and amines to convert primary hydroxyl groups of cellulose nanofibers into amide groups, eliminating the need for halogen and ionic substances, thereby enhancing heat resistance and compatibility with resins.

Benefits of technology

The method produces cellulose nanofibers with improved heat resistance, adhesion to resins, and compatibility, allowing for wider application in high-temperature environments without the environmental and industrial drawbacks of previous methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011911000010
    Figure 2025011911000010
  • Figure 2025011911000011
    Figure 2025011911000011
  • Figure 2025011911000012
    Figure 2025011911000012
Patent Text Reader

Abstract

To provide a method for hydrophobing a cellulose nanofiber which can obtain a cellulose nanofiber hydrophobed body that is excellent in heat resistance and adhesion to a resin without using a substance containing a halogen element and an ionic substance, and an excessive amount of a raw material in a cellulose nanofiber.SOLUTION: A method for hydrophobing a cellulose nanofiber includes mixing and dispersing raw material components containing at least a cellulose nanofiber, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer, and a polar organic solvent in the same system, substituting a primary hydroxyl group of a cellulose molecule constituting the cellulose nanofiber by an organic group containing a carbonyl group, then mixing and dispersing amine therein, and amidating the organic group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for hydrophobizing cellulose nanofibers, in which hydroxyl groups in cellulose nanofibers are hydrophobized by substituting them with organic compounds, and to a hydrophobized cellulose nanofiber. [Background technology]

[0002] In recent years, there has been a demand for lighter and smaller electronic materials such as semiconductors, optical materials, and capacitors in order to improve capacity and increase lamination, and there is also a demand for lighter, smaller, and thinner films to be used in these materials (see Patent Document 1).In addition, there is a demand for lighter onboard materials to improve fuel efficiency and driving range, and there is a demand for various resins used in vehicles to be lighter and maintain their strength at the same time (see Patent Document 2).

[0003] There is a demand for various films and resins to be thinner, smaller, and lighter, but it is not easy to achieve such thinning, miniaturization, and lighter weight while maintaining mechanical properties such as tensile strength and toughness.

[0004] 2. Description of the Related Art In recent years, attention has been focused on a technique for incorporating reinforcing fibers into a resin or film as a way of achieving both improved mechanical strength and reduced thickness and weight of various films and resins.

[0005] Reinforcing fibers include cellulose nanofibers, glass fibers, carbon fibers, and aramid fibers, and by incorporating a certain amount of any of these into a resin or film, the mechanical strength can be improved.

[0006] Among these, cellulose nanofibers are organic compounds, so if they can be uniformly dispersed and dissolved in resins and films, defects in appearance and the like can be prevented. In addition, cellulose nanofibers have the properties of high electrical insulation and a low coefficient of linear expansion (hereinafter also referred to as CTE), so they are expected to be applied to components that require insulation or measurability. Furthermore, when recycling resins and films containing reinforcing fibers, after they are scrapped, only cellulose nanofibers, which are organic compounds, can be automatically sorted using near-infrared rays among the reinforcing fibers described above, and they also have the advantage of being environmentally friendly (see Non-Patent Document 1).

[0007] For the above reasons, in recent years, there has been active research into incorporating cellulose nanofibers into resins and films to improve their properties (see Patent Document 3). However, due to the amphiphilicity of the hydroxyl groups in the cellulose molecules that make up the cellulose nanofibers, the cellulose molecules form hydrogen bonds with each other to produce aggregates of cellulose nanofibers, making them less compatible with, dispersible in, and bonded to organic compounds such as resins. Therefore, it is preferable to hydrophobize the hydroxyl groups on the outside of the cellulose molecules in advance.

[0008] The most widely used method for hydrophobizing cellulose nanofibers is the chemical fiberization method, in which the hydroxyl groups of cellulose nanofibers are carbonyl ionized using an oxidizing agent such as 2,2,6,6-tetramethyl-1-piperidine-N-oxy radical (hereinafter abbreviated as TEMPO), and then hydrophobized to form a carboxylic acid with a proton added, or hydrophobized by various functional group conversions (see Patent Document 4, and Non-Patent Documents 2 and 3).

[0009] The advantage of the hydrophobicity method using chemical fiberization with TEMPO is that the fiber units of the cellulose nanofibers are ionized, causing them to repel each other and inhibiting hydrogen bonds between the fibers, resulting in fibers in which each bundle is finely fiberized. Since the surface area is increased by finely fiberizing the fibers, good dispersibility is obtained when the fibers are impregnated into resins or films, and a significant improvement in functionality is observed.

[0010] However, disadvantages of the hydrophobization method using TEMPO include the fact that TEMPO itself is as expensive as or more expensive than precious metal catalysts, and even if only a small amount of catalyst is used, it will increase the price of the cellulose nanofiber material. In addition, in order to activate TEMPO, a co-catalyst material containing halogens or sodium is required, and therefore the cellulose nanofiber material also contains ions such as halogens and sodium. In addition, purification using large amounts of water is required to recover and wash TEMPO after the reaction is complete, which is disadvantageous in terms of price, environmental impact, and productivity.

[0011] In some cases, after hydrophobization using TEMPO, the material is washed with a large amount of aqueous solution to remove the halogens; however, the aqueous solution used often contains ions that trap the halogens, and even if the halogens are removed, the cellulose nanofiber material still ends up containing ionic substances, which is an issue.

[0012] If cellulose nanofiber material contains halogens or ionic substances, it becomes difficult to use it as a semiconductor material. Therefore, even if cellulose nanofibers can be defibrated, hydrophobized, and dispersed or incorporated into resins or films, there will be limitations to their applications.

[0013] Furthermore, when cellulose nanofibers are hydrophobized using TEMPO, the only terminal substituent that contributes to hydrophobization can be a carboxyl group, resulting in a lack of structural variety.

[0014] Furthermore, in the Celnol nanofiber compound obtained by the hydrophobization method using TEMPO, the primary hydroxyl groups are hydrophobized to carboxylic acid derivatives, but the heat resistance remains almost unchanged before and after hydrophobization, with a glass transition temperature (Tg) of 120°C and a 5% weight loss temperature (Td5) of about 200°C. These thermal properties are not sufficient for electronic applications that require high-heat processing processes, or for automotive material applications that require heat resistance, and there are issues with the heat resistance properties.

[0015] There have also been several reported cases in which cellulose nanofibers have been chemically defibrated and hydrophobized using materials that do not use TEMPO. For example, a method in which an excess amount of a base and an acid anhydride is reacted with cellulose nanofibers, or a method in which a halogenated ester is reacted with cellulose nanofibers to hydrophobize them, are known (see Patent Document 5).

[0016] However, the hydrophobization methods described in Patent Documents 4 and 5 both involve reactions that contain ionic substances such as halogens or use excessive amounts of raw materials relative to the cellulose nanofibers, and have issues in terms of efficiency, cost, and the environment when applied industrially.

[0017] There have been many developments of reactions that do not use TEMPO or ionic substances and use an equivalent amount of raw material to the cellulose nanofiber. For example, a reaction has been developed in which the cellulose nanofiber is reacted with an equivalent amount of acid anhydride in the presence of a nitrogen-based organic base catalyst to replace the primary hydroxyl groups of the cellulose nanofiber with ester groups to make it hydrophobic. This reaction does not contain halogens or ions and does not use an excessive amount of raw material, so it is expected to be industrialized. However, since the hydrophobic group of cellulose nanofiber is an ester group, there is a possibility that it will be applied in fields where the heat resistance and polarity brought about by the ester group can be tolerated, but there are still challenges to be overcome in applying it to fields where heat resistance of 220°C or more, which is the weight loss temperature (Td5) of the ester group, is generally required. [Prior art documents] [Patent documents]

[0018] [Patent Document 1] International Publication No. 2018 / 056459 [Patent Document 2] JP 2019-151782 A [Patent Document 3] JP 2022-159126 A [Patent Document 4] International Publication No. 2010 / 116794 [Patent Document 5] International Publication No. 2017 / 073700 [Non-patent literature]

[0019] [Non-Patent Document 1] Tamaki Kojima, Panasonic Technical Journal, 57, 1, (2011) [Non-Patent Document 2] Isogai, A.: Kobunshi, 58, 90(2009) [Non-Patent Document 3] Isogai, A., Saito, T.: Biopla J., 29, 12(2010) Summary of the Invention [Problem to be solved by the invention]

[0020] In order to disperse, dissolve, and incorporate cellulose nanofibers into resins and films, it is preferable to hydrophobize the hydroxyl groups of the cellulose nanofibers and prevent the formation of hydrogen bonds and aggregates between the cellulose nanofibers. However, the conventional hydrophobization methods described above have problems such as the inclusion of halogens and ions in the cellulose nanofiber material after hydrophobization, the high cost and high production process, which are industrially disadvantageous, and the need for large amounts of materials and wastewater treatment, which are environmentally disadvantageous.

[0021] The present invention has been made in consideration of the above-mentioned problems in the conventional art, and its object is to provide a method for hydrophobizing cellulose nanofibers that does not use substances containing halogen elements or ionic substances, and does not use excessive amounts of raw materials relative to the cellulose nanofiber, and that can produce hydrophobic cellulose nanofibers that have excellent heat resistance and adhesion to resins, and to provide hydrophobic cellulose nanofibers that have excellent compatibility and adhesion to resins and are highly heat resistant. [Means for solving the problem]

[0022] In order to solve the above-mentioned problems, the present inventors have sincerely studied and discovered a method for hydrophobizing cellulose nanofibers using reaction raw materials, catalysts, and solvents that do not contain halogens or ions. In addition, amide groups, which have better heat resistance and compatibility than carboxylic acids and esters, are introduced into the hydrophobic groups of the hydrophobized cellulose nanofibers thus obtained. This eliminates the use restrictions, production process, and environmental issues caused by the presence of halogens and ions, and makes it possible to apply the cellulose nanofibers to heat-resistant materials that require a weight loss temperature (Td5) of 220°C or higher. That is, one aspect of the present invention that solves the above problems is as follows.

[0023] (1) A method for hydrophobizing cellulose nanofibers, comprising mixing and dispersing raw material components containing at least cellulose nanofibers, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer, and a polar organic solvent in the same system, replacing the primary hydroxyl groups of the cellulose molecules constituting the cellulose nanofibers with organic groups containing a carbonyl group, and then mixing and dispersing an amine to amidate the organic groups.

[0024] (2) The method for hydrophobizing cellulose nanofibers described in (1) above, wherein the carbonyl group-containing monomer or the carboxylic acid group-containing monomer and the amine are 1 to 100 parts by mass per 100 parts by mass of the cellulose nanofibers and the polar organic solvent combined.

[0025] (3) The method for hydrophobizing cellulose nanofibers according to (1) or (2) above, wherein the carbonyl group-containing monomer or the carboxylic acid group-containing monomer is one selected from the group consisting of aliphatic ring-opened carboxylic acids, aliphatic acid anhydrides, aliphatic acid dianhydrides, aromatic acid anhydrides, aromatic acid dianhydrides, and bis-aromatic acid dianhydrides.

[0026] (4) The method for hydrophobizing cellulose nanofibers according to any one of (1) to (3) above, wherein the amine is one selected from the group consisting of aliphatic amines, aromatic amines, and ether amines.

[0027] (5) The method for hydrophobizing cellulose nanofibers according to any one of (1) to (4), wherein the raw material components further contain one catalyst selected from the group consisting of organic base catalysts, Bronsted acid catalysts, and metal catalysts.

[0028] (6) The method for hydrophobizing cellulose nanofibers according to (5) above, wherein the one catalyst selected from the group consisting of organic base catalysts, Bronsted acid catalysts, and metal catalysts is present in an amount of 0.01 to 0.5 parts by mass per 100 parts by mass of the cellulose nanofibers and the polar organic solvent combined.

[0029] (7) The method for hydrophobizing cellulose nanofibers according to (5) or (6) above, wherein the organic base catalyst is a nitrogen-containing organic compound.

[0030] (8) The method for hydrophobizing cellulose nanofibers according to any one of (1) to (7), wherein the raw material components further contain a base.

[0031] (9) The method for hydrophobizing cellulose nanofibers according to (8) above, wherein the base is a nitrogen-containing organic compound.

[0032] (10) The method for hydrophobizing cellulose nanofibers according to any one of (1) to (9), wherein the cellulose nanofibers are a cellulose nanofiber solution obtained by solvent-substitution of an aqueous dispersion of cellulose nanofibers having a non-volatile content of 10% by mass or less with a polar organic solvent.

[0033] (11) The method for hydrophobizing cellulose nanofibers according to any one of (1) to (10), wherein the cellulose nanofibers have a fiber diameter of 1 to 1000 nm, and the hydrophobized cellulose nanofibers have a fiber diameter of 1 to 300 nm.

[0034] (12) The method for hydrophobizing cellulose nanofibers according to any one of (1) to (11) above, wherein the raw material components do not contain any halogen-containing substances, cation-containing substances, or anion-containing substances.

[0035] (13) A hydrophobized cellulose nanofiber represented by the following general formula (III): [ka] [In general formula (III), R 1 represents a divalent carbonyl-containing aliphatic group or a divalent carbonyl-containing aromatic group; R 2 represents a divalent aliphatic group or a divalent aromatic group, either of which may have a substituent, and n represents an integer of 10 to 500,000. Effect of the Invention

[0036] According to the present invention, it is possible to provide a method for hydrophobizing cellulose nanofibers that does not use substances containing halogen elements or ionic substances, and does not use excessive amounts of raw materials relative to the cellulose nanofiber, and that can produce hydrophobic cellulose nanofibers that have excellent heat resistance and adhesion to resins, as well as hydrophobic cellulose nanofibers that have excellent compatibility and adhesion to resins and are highly heat resistant. [Brief description of the drawings]

[0037] [Figure 1] FIG. 2 shows the infrared absorption spectrum of the hydrophobized cellulose nanofiber obtained in Example 1. [Diagram 2] FIG. 2 shows an infrared absorption spectrum of the hydrophobic cellulose nanofiber obtained in Example 2. [Diagram 3] FIG. 1 shows an infrared absorption spectrum of the hydrophobized cellulose nanofiber obtained in Example 6. [Figure 4] FIG. 2 shows an infrared absorption spectrum of the hydrophobized cellulose nanofiber obtained in Comparative Example 1. [Diagram 5] FIG. 2 shows an infrared absorption spectrum of the hydrophobized cellulose nanofiber obtained in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] <Method for making cellulose nanofibers hydrophobic> The method for hydrophobizing cellulose nanofibers of this embodiment is characterized by mixing and dispersing raw material components containing at least cellulose nanofibers, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer, and a polar organic solvent in the same system, replacing the primary hydroxyl groups of the cellulose molecules that make up the cellulose nanofibers with organic groups containing a carbonyl group, and then mixing and dispersing an amine to amidate the organic groups.

[0039] In this embodiment, the raw material unhydrophobized cellulose nanofibers are first reacted with a carbonyl group-containing monomer or a carboxylic acid group-containing monomer to hydrophobize the primary hydroxyl groups of the cellulose nanofibers by substituting carboxylic acid groups or ester groups. The carboxylic acid groups or ester groups are then amidated by further reacting with an amine. This makes it possible to obtain hydrophobized cellulose nanofibers that do not contain halogens or ions.

[0040] In the method for hydrophobizing cellulose nanofibers of this embodiment, at least cellulose nanofibers, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer, a polar organic solvent, and an amine are used as raw materials. That is, cellulose nanofibers can be hydrophobized without using a substance containing a halogen element or an ionic substance. In addition, since there is no need to use an expensive catalyst such as TEMPO, it is possible to realize hydrophobization of cellulose nanofibers at low cost. Furthermore, when hydrophobizing using TEMPO, the only substituent at the end is a carboxyl group, but in this embodiment, there are many types of substituent at the end that contribute to hydrophobization, and there is a wide variety in structure. In addition, in this embodiment, the hydroxyl groups held by the cellulose nanofibers can be hydrophobized using cellulose nanofibers, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer in an amount equivalent to the amount of substance of the cellulose nanofiber, and a catalyst and a solvent in an amount less than the amount of substance of the cellulose nanofiber. Furthermore, since the hydrophobized cellulose nanofiber obtained by this embodiment has an amide group, it has high heat resistance and adhesion to resins.

[0041] Without being bound by theory, by hydrophobizing the hydroxyl groups of cellulose nanofibers, it is possible to suppress the action of hydrogen bonding and aggregation between cellulose nanofiber units via the hydroxyl groups, making it easier to disperse and dissolve in various resins and varnishes. Furthermore, when cellulose nanofibers are dispersed and dissolved in resins and varnishes, even if the diameter of the cellulose nanofibers reaches about 1000 nm, the cellulose nanofiber material can fully exert a network effect when used in resins and varnishes or when made into films, thereby improving tensile strength and elastic modulus. Similarly, it can also be effective in suppressing thermal expansion.

[0042] By dispersing or dissolving the hydrophobic cellulose nanofibers obtained by this embodiment in any resin or varnish and coating or molding the resulting material, the tensile strength and elastic modulus of a film or molded product made from the original resin or varnish can be improved by 1.5 times or more.Similarly, by dispersing or dissolving the hydrophobic cellulose nanofibers obtained by this embodiment in any resin or varnish and coating or molding the resulting material, the thermal expansion coefficient of a film or molded product made from the original resin or varnish can be reduced by 20% or more.

[0043] The hydrophobized cellulose nanofiber obtained by this embodiment has improved heat resistance of the cellulose nanofiber alone compared to cellulose nanofibers that have not been hydrophobized or cellulose nanofibers in which the hydrophobic groups have been substituted with carboxylic acid groups or ester groups. The glass transition temperature of the hydrophobized cellulose nanofiber obtained by this embodiment is higher by 50°C or more compared to cellulose nanofibers that have not been hydrophobized or cellulose nanofibers in which the hydrophobic groups have been substituted with carboxylic acid groups or ester groups. Similarly, when a resin molded product or film is coated with a resin in which the hydrophobized cellulose nanofiber obtained by this embodiment is dispersed and impregnated, the heat resistance is improved compared to a resin molded product or film impregnated with cellulose nanofibers that have not been hydrophobized, or cellulose nanofibers in which a carboxylic acid group or an ester group has been substituted for the hydrophobic group. The heat resistance is also improved compared to a resin molded product or film in which no cellulose nanofiber is impregnated at all. Although not bound by theory, the heat decomposition temperature of the amide group is higher than that of the hydroxyl group, carboxylic acid group, or ester group before hydrophobization, and the heat resistance is improved by impregnating the cellulose nanofiber substituted with the amide group. In addition, the amide group has a higher polarity than the hydroxyl group, carboxylic acid group, or ester group before hydrophobization, and the compatibility with the base resin is improved, so it is presumed that the increase in the network effect due to the improvement in dispersibility also helps to improve the heat resistance.

[0044] The fiber diameter of the hydrophobic cellulose nanofiber obtained by this embodiment can be 1 to 300 nm. Although the fiber diameter of cellulose nanofibers hydrophobized using conventional catalysts can be as small as about 5 nm, the hydrophobic cellulose nanofiber obtained by this embodiment has the same dispersibility and compatibility with resins as conventional hydrophobic cellulose nanofibers, even if the fiber diameter is larger.

[0045] As described above, in this embodiment, first, the raw material unhydrophobized cellulose nanofibers are reacted with a carbonyl group-containing monomer or a carboxylic acid group-containing monomer to replace the primary hydroxyl groups of the cellulose nanofibers with carboxylic acid groups or ester groups, and hereinafter, the product obtained by replacing with carboxylic acid groups or ester groups is referred to as an intermediate. Then, the intermediate is reacted with an amine to convert the ester groups to amide groups to obtain hydrophobized cellulose nanofibers. The reaction scheme of the hydrophobization method of the present embodiment is shown below. Here, the process up to producing the intermediate is referred to as the "pre-process", and the process up to producing the hydrophobized cellulose nanofibers, which are the final product, is referred to as the "post-process".

[0046] [ka]

[0047] 《Pre-process》 First, each component among the raw material components used in the production of the intermediate in the previous step will be described below.

[0048] [Cellulose nanofiber] The cellulose polymer that constitutes the cellulose nanofiber used as the raw material is represented by the following general formula (I).

[0049] [ka] [In general formula (I), n represents an integer of 10 to 500,000.]

[0050] The type of cellulose nanofiber used in this embodiment is not particularly limited, but pulp or cellulose nanofibers defibrated from pulp can be used. In order to efficiently react with various organic materials, the cellulose nanofibers are preferably defibrated products. Furthermore, mechanically defibrated products can be used as defibrated products of cellulose nanofibers.

[0051] Cellulose nanofibers generally contain moisture, and the moisture concentration may reach 99% by mass (there is no problem if the mechanically defibrated cellulose nanofiber product has a non-volatile content of 1% by mass or more). If the hydrophobic cellulose nanofiber obtained according to this embodiment is dispersed in a solvent, it can be processed into a film by solvent coating or the like, so the raw cellulose nanofiber may be, for example, an aqueous dispersion mechanically defibrated from pulp.

[0052] Furthermore, a step of replacing the water contained in the cellulose nanofiber with any organic solvent and dehydrating the cellulose nanofiber may be provided before carrying out the hydrophobization reaction. That is, in this embodiment, a cellulose nanofiber solution obtained by replacing an aqueous dispersion of cellulose nanofibers with a nonvolatile content of 10% by mass or less with a polar organic solvent can be used as the cellulose nanofiber. Usually, an aqueous dispersion of cellulose nanofibers mechanically defibrated from pulp has a moist creamy or paste-like appearance even when the nonvolatile content of the cellulose nanofiber is about 5% by mass (water content is about 95%). Even in this case, there is no problem as long as the cellulose nanofibers can be uniformly dispersed in the solvent when diluted with an organic solvent and subjected to solvent replacement (dehydration).

[0053] When replacing the water contained in cellulose nanofibers with any polar organic solvent, the cellulose nanofibers are first dispersed and dissolved in any organic solvent. The water originally contained in the cellulose nanofibers is then removed by distillation to obtain a cellulose nanofiber / organic solvent solution that does not contain water molecules. Without being bound by theory, it is believed that if cellulose nanofibers are heated and dehydrated alone without a distillation process, the molecules of the cellulose nanofibers will irreversibly aggregate via hydrogen bonds as they are dehydrated. It is also believed that dehydrating the water molecules allows the reactions to proceed more efficiently in subsequent processes because various materials are not hindered by the water molecules.

[0054] The non-volatile content of the cellulose nanofibers substituted and dispersed in a polar solvent used in this embodiment is not particularly limited, but may be 50% by mass or less, 5% by mass or less, 1% by mass or less, or 0.5% by mass or less. Generally, commercially available cellulose nanofibers have a non-volatile content of 5% by mass, so when substituted and dispersed in a solvent, the non-volatile content is often 5% by mass or less.

[0055] Next, the fiber diameter of the cellulose nanofiber used as the raw material will be described. The fiber diameter of the cellulose nanofiber used in the cellulose nanofiber-containing resin is not particularly limited, but may be 1 to 1000 nm or 5 to 500 nm. Without being bound by theory, it is believed that the smaller the fiber diameter, the less aggregation occurs due to hydrogen bonding between hydroxyl groups of the cellulose nanofiber, and the larger the surface area becomes, which increases the efficiency of hydrophobizing the hydroxyl groups of the cellulose nanofiber.

[0056] Various definitions of the fiber diameter of cellulose nanofibers have been proposed by various research institutes and papers, but in this embodiment, the maximum central fiber diameter of a single cellulose fiber is 1 μm or less, and the branched portion of the fiber includes a fiber diameter of 1 to 50 nm. The method for measuring the fiber diameter of cellulose nanofibers will be described later.

[0057] The fiber length of the cellulose nanofibers used in this embodiment is not particularly limited, but may be 100 nm or more, 500 nm or more, 1000 nm (1 μm) or more, or 1,000,000 nm (1 mm) or more. Without being bound by theory, it is expected that the longer the fiber length, the more the mesh-like networking will progress in the resin or film to which it is added, and the tensile strength of the molded product or film will improve.

[0058] [Polar solvent] The polar solvent used in this embodiment is preferably a solvent in which the cellulose nanofibers disperse when the water molecules in the cellulose nanofibers are replaced with an organic solvent by distillation. The polar solvent is not particularly limited, but is preferably a solvent with a boiling point higher than that of water. Examples include nitrogen-containing solvents such as N-methyl-2-pyrrolidone (N-methylpyrrolidone), N,N'-dimethylacetamide, N,N'-dimethylformamide, 2-vinylpyridine, and 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidine; sulfur-containing solvents such as dimethyl sulfoxide, diethyl sulfoxide, dimethyl sulfone, ethyl methyl sulfone, and sulfolane; ether-based solvents such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, and triethylene glycol diethyl ether; and ester-based solvents such as γ-butyrolactone and cellosolve acetate.

[0059] [Carbonyl group-containing monomers, carboxylic acid group-containing monomers] In this embodiment, when producing an intermediate of cellulose nanofibers, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer is used as a hydrophobic reactant to be substituted with a hydroxyl group. Examples of the carbonyl group-containing monomer include acetic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, pyromellitic anhydride, carbonyl diphthalic anhydride, trimellitic anhydride, cyclohexane tetracarboxylic anhydride, tetrahydrophthalic anhydride, norbornene phthalic anhydride, octenyl succinic anhydride, dicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride, 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, and 4,4'-oxydiphthalic anhydride. Examples of the carboxylic acid group-containing monomer include monomers containing a group derived from a carboxylic acid such as succinic acid, propionic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, 1,9-nonanedicarboxylic acid, dodecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, octadecanedioic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, decahydro-1,4-naphthalenedicarboxylic acid, (1a,2a,4a)-1,2,4-cyclohexanetricarboxylic acid, 1,2,4,5-cyclohexanetetracarboxylic acid, phthalic acid, terephthalic acid, isophthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and acenaphthylene-5,6-dicarboxylic acid. Among them, the carbonyl group-containing monomer or the carboxylic acid group-containing monomer is preferably one selected from the group consisting of aliphatic ring-opening carboxylic acids, aliphatic acid anhydrides, aliphatic acid dianhydrides, aromatic acid anhydrides, aromatic acid dianhydrides, and bis-aromatic acid dianhydrides. From the viewpoint of improving heat resistance, those having an aromatic group, such as phthalic acid and terephthalic acid, are preferred.

[0060] In this embodiment, the primary hydroxyl groups of the cellulose molecules constituting the cellulose nanofibers are replaced with carbonyl group-containing monomer residues or carboxylic acid group-containing monomer residues. As described above, when cellulose nanofibers are hydrophobized using TEMPO, the only terminal substituent that contributes to hydrophobization is the carboxyl group. In contrast, in this embodiment, the terminal substituents differ depending on the carbonyl group-containing monomer or carboxylic acid group-containing monomer used, resulting in a wide variety of structures.

[0061] In this embodiment, it is not necessary to use an excessive amount of the carbonyl group-containing monomer or the carboxylic acid group-containing monomer relative to the cellulose nanofibers, and the amount is preferably 80 to 120 parts by mass, more preferably 90 to 110 parts by mass, and even more preferably 95 to 105 parts by mass, relative to 100 parts by mass of the cellulose nanofibers.

[0062] [catalyst] In this embodiment, the raw material component preferably further contains at least one catalyst selected from the group consisting of an organic base catalyst, a Bronsted acid catalyst, and a metal catalyst. Without being bound by theory, it is expected that the electrophilicity of the hydrophobization reactant is increased by activating the catalyst by coordinating with the carbonyl group-containing monomer or the carboxylic acid group-containing monomer, which is the hydrophobization reactant, and the substitution with the hydroxyl group of the cellulose nanofiber will progress more efficiently. The catalyst is not particularly limited as long as it has a coordination effect with the carbonyl, but it is preferable to use an organic base catalyst, a Bronsted acid catalyst, or a metal catalyst. However, in order to prevent the incorporation of halogens or ionic substances into the reaction system, it is preferable to select a non-halogen, non-ionic substance as the catalyst. Examples of Bronsted acid catalysts include sulfuric acid, p-toluenesulfonic acid, and methanesulfonic acid. Examples of the organic base catalyst include 4-dimethylaminopyridine, 1,8-diazabicyclo[5,4,0]undecene-7, 1,5-diazabicyclo[4,3,0]nonene-5, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, methyltriamylammonium hydroxide, methyltributylammonium hydroxide, etc. As the organic base catalyst, nitrogen-containing organic compounds such as amine compounds are preferred. Examples of metal catalysts include zinc acetate (II), zinc nitrate (II), zinc carbonate (II), cobalt acetate (II), cobalt hydroxide (II), cobalt nitrate (II), cobalt sulfate (II), cobalt carbonate (II), boric acid, isobutylboronic acid, phenylboronic acid, 1-naphthaleneboronic acid, tetra-i-propoxytitanium, antimony trioxide, triphenylantimony, triphenylantimony diacetate, dibutyltin, dibutyltin bis, sodium hydrogen carbonate, etc. These may be used alone or in combination of two or more.

[0063] The amount (mass ratio) of catalyst to be blended with respect to cellulose nanofibers is preferably 1 to 20 parts by mass, more preferably 1 to 15 parts by mass, and more preferably 1 to 10 parts by mass, per 100 parts by mass of cellulose nanofibers. Without being bound by theory, if the amount of catalyst is too small, the efficiency of hydrophobization decreases, whereas if the amount of catalyst is too large, there is concern about side reactions such as homopolymerization of the hydrophobization reaction product.

[0064] [base] In this embodiment, it is preferable that the raw material components further contain a base. Although not bound by theory, it is expected that the base activates the protons of the hydroxyl groups of the cellulose nanofibers, thereby improving the reactivity of the cellulose nanofibers. Examples of bases include pyridine, triethylamine, 1,4-diazabicyclo[2,2,2]octane, N-ethyldiisopropylamine, 2,6-dimethylpyridine, tetramethylammonium hydroxide, sodium ethoxide, potassium-t-butoxide, lithium diisopropylamide, potassium hexamethyldisilazide, and the like. These may be used alone or in combination of two or more. In addition, although these are not particularly limited, it is more preferable to use an amine compound (nitrogen-containing organic compound) from the viewpoint of preventing the inclusion of alkaline ionic substances.

[0065] The amount (mass ratio) of the base to the cellulose nanofiber is preferably 0 to 100 parts, and more preferably 1 to 50 parts, based on the mass equivalent of the cellulose nanofiber. Without being bound by theory, the hydrophobization reaction proceeds even in the absence of a base, but the incorporation of a base can activate the hydroxyl groups of the cellulose nanofiber, thereby improving the efficiency of hydrophobization.

[0066] In this embodiment, it is preferable that one or both of the organic base catalyst and the base are nitrogen-containing organic compounds, since no halogen or ionic substance is used.

[0067] The above raw material components can be prepared so as not to contain halogen-containing substances, cation-containing substances, or anion-containing substances. Therefore, the hydrophobized cellulose nanofiber obtained by this embodiment can be used for applications such as semiconductor materials where contamination with halogens or ionic substances is to be avoided.

[0068] The blending amount (mass ratio) of the carbonyl group-containing monomer or carboxylic acid group-containing monomer as the hydrophobization reactant relative to the total of 100 parts by mass of the cellulose nanofiber and the polar organic solvent is preferably 1 to 20 parts by mass, more preferably 1 to 10 parts by mass, and more preferably 1 to 2 parts by mass, based on the cellulose nanofiber mass equivalent. Although not bound by theory, when the amount of the hydrophobization reactant is large, there is a concern that unreacted acid anhydride, carboxylic acid, or amine remains in the system and cannot be completely removed by post-treatment. In addition, when the hydrophobized cellulose nanofiber obtained by this embodiment is used to further carry out a reaction by functional group conversion (when carrying out amidation, imidization, urethanization, olefin addition, etc.), there is also a concern that the remaining acid anhydride, carboxylic acid, or amine may induce a side reaction.

[0069] Without being bound by theory, for example, when producing an intermediate (general formula (II)), if the amount of the hydrophobization reactant carbonyl group-containing monomer or carboxylic acid group-containing monomer is too large, they may remain. In that case, there is a concern that they may induce side reactions or inhibit the reaction when producing the hydrophobized cellulose nanofiber (general formula (III)) in the subsequent process in which the amide groups are hydrophobized.

[0070] The above raw material components are used to produce an intermediate, the structure of which is represented by the following general formula (II).

[0071] [ka] [In general formula (II), R 1 represents a hydroxyl group, or an aliphatic or aromatic carboxylic acid group, each of which may have a substituent, and n represents an integer of 10 to 500,000.

[0072] In the general formula (II), n is the repeating number of the monomer in [ ] and represents an integer of 10 to 500,000, preferably 100 to 100,000, and more preferably 1,000 to 100,000. The same applies to n in the above-mentioned general formula (I).

[0073] In general formula (II), R 1 The aliphatic carboxylic acid group represented by the formula (I) is an aliphatic carboxylic acid group having 1 to 50 carbon atoms. 1 Examples of the aromatic carboxylic acid group represented by the formula (I) include aromatic carboxylic acid groups having a carbon number of 7 to 50. When the aliphatic carboxylic acid group and the aromatic group have a substituent, examples of the substituent include a monoamino group and a diamine.

[0074] In general formula (II), R 1 An example of this is -C x H (2x+1) COOH, -CHCOOH, -C x H (2x+1) CONHC y H (2y+1) NH2, -C6H4CONHC y H (2y+1) Here, x is an integer of 1 to 50, and y is an integer of 2 to 50.

[0075] In this embodiment, an example of a process for producing an intermediate is a process in which a carbonyl group-containing monomer or a carboxylic acid group-containing monomer, a polar organic solvent, a catalyst, and a base are appropriately selected and mixed into a cellulose nanofiber solution that has been solvent-substituted as described above, and then the mixture is poured into a sealed flask or the like. By adjusting the stirring and temperature and reacting at an appropriate time, a hydrophobic cellulose nanofiber can be obtained.

[0076] When the intermediate is produced, the reaction temperature may be room temperature or may be heated. When heated, the temperature may be 40° C. or higher and 250° C. or lower, or 40° C. or higher and 200° C. or lower. Although not bound by theory, since cellulose nanofibers have a risk of decomposition and aggregation at high temperatures, the reaction temperature is preferably 250° C. or lower, and more preferably 200° C. or lower.

[0077] In addition, when the intermediate is produced, it is preferable to produce the intermediate while stirring the reaction solution. The stirring speed is not particularly limited, but may be 50 rpm to 10,000 rpm, 100 rpm to 7,500 rpm, or 250 rpm to 5,000 rpm. Although not bound by theory, the fiber units of the cellulose nanofibers are defibrated by stirring in a solution, and the aggregation of the fiber units can be suppressed. In addition, by improving the dispersibility and preventing the aggregation of the fiber units, the surface area of ​​the cellulose nanofibers is increased, and it is expected that the efficiency of hydrophobization will be improved.

[0078] The reaction time for producing the intermediate may be from 5 hours to 48 hours, from 10 hours to 36 hours, or from 15 hours to 24 hours.

[0079] The gas in the reaction system when the intermediate is produced is not particularly limited, and may be air or an inert atmosphere such as nitrogen.

[0080] It is preferable to seal the reaction vessel when producing the intermediate. When heating the flask, it is possible to place a Dimroth condenser on the top of the flask, but it is preferable to plug the top of the Dimroth condenser. This is to prevent water molecules from coordinating and adhering to the hydrophobized cellulose nanofibers due to the inclusion of excess air from the outside.

[0081] 《Post-process》 After producing an intermediate in the first step, the intermediate is reacted with an amine in the second step to obtain the final product, hydrophobized cellulose nanofibers represented by the following general formula (III).

[0082] [ka] [In general formula (III), R 1 represents a divalent carbonyl-containing aliphatic group or a divalent carbonyl-containing aromatic group; R 2 represents a divalent aliphatic group or a divalent aromatic group, either of which may have a substituent, and n represents an integer of 10 to 500,000.

[0083] In addition, R of the intermediate general formula (II) 1 When R is a hydroxyl group (OH), R of the hydrophobized cellulose nanofiber represented by the above general formula (III) 1 The hydroxyl group disappears and an amide group is directly introduced.

[0084] In the general formula (III), R 1 , R 2 This will be explained later in the description of the hydrophobized cellulose nanofiber of this embodiment.

[0085] [Amine] In this embodiment, the amine to be reacted with the carbonyl group of the intermediate is preferably one selected from the group consisting of aliphatic amines, aromatic amines, and ether amines. Examples of the amine include ethylenediamine, N-methylethylenediamine, N-isopropylethylenediamine, N,N-diisopropylethylenediamine, and N,N-bis(3-aminopropyl)ethylenediamine. Examples of aromatic diamines include 1,2-diphenylethylenediamine, 1,2-diamino-2-methylpropane, 2,3-diamino-naphthalene, N-butylethylenediamine, N-acetylethylenediamine, adamantane-1,3-diamine, N-(2-hydroxypropyl)ethylenediamine, N-(3-aminopropyl)cyclohexylamine, N-benzyl-1,3-propanediamine, and 2,3,5,6-tetraphenylene. Examples of the diamine include diamines such as fluoro-1,4-phenylenediamine, 1,4-cyclohexanediamine, 1,4-phenylenediamine, 4-bromo-1,2-phenylenediamine, 4-nitro-1,2-phenylenediamine, 4-methyl-N-(3-phenylpropyl)-1,2-phenylenediamine, N-benzylethylenediamine, norbornanediamine, benzylamine, and phenylene ether diamine; and monoamines such as propylamine, butylamine, hexylamine, and aniline. Among these, it is preferable to use aromatic amines and aromatic diamines from the viewpoint of improving heat resistance.

[0086] In this embodiment, a catalyst may be used when producing the hydrophobized cellulose nanofiber (general formula (III)). Without being bound by theory, it is expected that the catalyst will coordinate to the terminal carbonyl of the intermediate (general formula (II)) of the hydrophobized cellulose nanofiber obtained earlier, thereby increasing the electrophilicity of the intermediate, thereby promoting the amidation reaction. There are no particular limitations on the catalyst as long as it has a coordination effect on the carbonyl group, but a catalyst that has been recognized to be effective in promoting amidation is preferable. However, in order to prevent the incorporation of halogens or ionic substances into the reaction system, it is preferable to select a non-halogen, non-ionic substance as the catalyst. The catalyst used in the reaction with the carbonyl group-containing monomer or carboxylic acid group-containing monomer described above can be used continuously, but new catalysts that are expected to promote condensation and accelerate amidation include dicyclohexylcarbodiimide, diisopropylcarbodiimide, 1-hydroxybenzotriazole, 1-hydroxy-7-azabenzotriazole, N-hydroxysuccinimide, N,N-succinimide carbonate, ethyl cyanohydroxyiminoacetate, N-methylimidazole, N,N-carbonyldiimidazole, and N,N-dimethyl-4-aminopyridine N-oxide.

[0087] As the conditions for reacting the intermediate with an amine in the subsequent step, the conditions for producing the intermediate from the above-mentioned raw material components can be applied as they are. However, when producing the final product, hydrophobized cellulose nanofibers (general formula (III)), if the amount of amine, which is the hydrophobization reactant, is too large, the amine will remain, which may induce side reactions or become an inhibitory factor when further modifying the hydrophobized cellulose nanofibers (general formula (III)) in which the amide groups have been hydrophobized.

[0088] In this manner, the final product, hydrophobized cellulose nanofibers represented by general formula (III), is obtained.

[0089] The hydrophobic cellulose nanofiber obtained by this embodiment is dispersed in an organic solvent, and therefore the obtained organic solvent dispersion can be used as is when it is desired to use it as a raw material for further functional group conversion, when it is desired to mix and disperse it with other varnish materials, or when it is desired to form it into a film by solvent coating.

[0090] When it is desired to recover the hydrophobized cellulose nanofibers obtained by this embodiment as a solid content, the method is not particularly limited, and desolvation and recovery of the solid content of the hydrophobized cellulose nanofibers can be carried out by existing methods, such as a method of recovering the hydrophobized cellulose nanofibers remaining on filter paper by suction filtration, a method of volatilizing the solvent using a pressure reducing device such as an evaporator, and a method of using a centrifuge.

[0091] When resin molding or film coating is carried out using a resin in which cellulose nanofibers substituted with any hydrophobic group obtained by this embodiment are dispersed, dissolved, or impregnated, a material is obtained that does not produce holes, bumps, or cracks, compared to resin moldings or films impregnated with cellulose nanofibers that have not been hydrophobized.

[0092] When a resin obtained by this embodiment in which cellulose nanofibers substituted with any hydrophobic group are dispersed, dissolved, or impregnated is used to coat a resin molding or film, the tensile strength is improved by 1.5 times or more compared to a resin molding or film impregnated with cellulose nanofibers that have not been hydrophobized, and is improved by 2 times or more compared to a resin molding or film not impregnated with cellulose nanofibers at all.

[0093] When a resin obtained by this embodiment in which cellulose nanofibers substituted with any hydrophobic group are dispersed, dissolved, or impregnated is used to coat a resin molding or film, the coefficient of linear expansion (hereinafter, CTE) is reduced by 20% or more compared to a resin molding or film impregnated with cellulose nanofibers that have not been hydrophobized. In addition, when the CTE is compared to a resin molding or film not impregnated with cellulose nanofibers at all, it is reduced by 50% or more.

[0094] Cellulose nanofibers substituted with arbitrary hydrophobic groups obtained by the hydrophobization method of this embodiment can reduce the cost of the hydrophobization process to 1 / 10 of that of cellulose nanofibers obtained by conventional hydrophobization methods, and can also reduce the levels of ions such as halogens and sodium contained in the cellulose nanofibers to below the detection limit.

[0095] <Analysis method of hydrophobized cellulose nanofibers according to the present embodiment> The hydrophobic cellulose nanofibers obtained by the method for hydrophobizing cellulose nanofibers according to the present embodiment can be analyzed by a Fourier transform infrared spectrophotometer (FT-IR). The infrared absorption wavelength of the carbonyl derived from the ester group and carboxylic acid group generated by the hydrophobization is measured at 1700 cm -1 In addition, if the hydrophobicization process for cellulose nanofibers is carried out in a closed system and the entire process from preparation to analysis is carried out in a manner that prevents water from entering from the outside, the hydrophobicity of the cellulose nanofibers can be confirmed at 3500 cm -1 A decrease in the infrared absorption wavelength of the hydroxyl group (-OH) can be confirmed before and after hydrophobization. Although some water molecules that could not be removed from the cellulose nanofiber and adsorption of water molecules in the reaction vessel are considered to be involved, if the hydrophobization process is progressing, the primary hydroxyl groups, which account for one-third of the hydroxyl groups in the cellulose nanofiber, are substituted and hydrophobized, and the 3500 cm -1 It can be seen that the infrared absorption wavelength area of ​​the hydroxyl group (-OH), which can be seen before and after, is reduced by about 1 / 3.

[0096] <Method for analyzing fiber diameter of hydrophobic cellulose nanofiber> When analyzing the fiber diameter of the hydrophobized cellulose nanofiber obtained by the cellulose nanofiber hydrophobization method according to the present embodiment, a scanning electron microscope (SEM) can be used, although the analysis method is not limited thereto. When analyzing a sample using SEM, it is usually necessary to collect the sample as a solid and dry the solid sample to volatilize the solvent and water contained in the sample, but the sample can be obtained by an existing method. For example, as described in the examples described later, the hydrophobized cellulose nanofiber after production can be collected on a filter paper by suction filtration, and then dried in a heating dryer at 60°C for about 2 hours to obtain the sample. Although not bound by theory, cellulose nanofibers may irreversibly aggregate due to high-temperature heating or rapid heating, and the fiber diameter may become thicker than immediately after production, so heating is preferably at 100°C for 2 hours or less, more preferably at 80°C for 2 hours or less, and more preferably at 60°C for 2 hours or less.

[0097] The fiber diameter of the dried sample of the hydrophobized cellulose nanofiber obtained as described above can be analyzed by observing it with an SEM.

[0098] <Solvent replacement of cellulose nanofiber aqueous dispersion> As described above, when an aqueous dispersion of cellulose nanofibers mechanically defibrated from pulp is used as a raw material, it is preferable to dehydrate the cellulose nanofibers and disperse them in an organic solvent. An example of solvent replacement for an aqueous dispersion of cellulose nanofibers is shown below.

[0099] 10-50g of cellulose nanofiber water dispersion (Mori Machinery Corporation, Cell Film C-500, NV5%) is added to a 300mL separable flask, and 100-200g of dimethyl sulfoxide (DMSO) is added thereto, and then the separable flask is covered. A stirrer, thermometer, nitrogen inlet tube, fractionating column, cooling tube, and distillate receiving flask are placed on the top of the flask to form a distillation apparatus, and then heated with a mantle heater or oil bath. The temperature inside the flask is set to 100-130°C, and heating and stirring are performed for 3-10 hours. The process is completed when the theoretical amount of water coordinated to or contained in the cellulose nanofibers is collected in the distillate flask. The cellulose nanofiber solvent dispersion remaining in the separable flask is collected and used as the cellulose nanofiber raw material before hydrophobization.

[0100] Furthermore, the cellulose nanofiber raw material obtained as described above can be further defibrated by stirring it in a high-pressure homogenizer at 10,000 rpm for 10 to 30 minutes, or by subjecting it to ultrasonic treatment in an ultrasonic homogenizer for 10 to 30 minutes.

[0101] Alternatively, a solvent dispersion of defibrated cellulose nanofibers can be obtained and used as is. Also, cellulose nanofiber pulp can be used to hydrophobize the cellulose nanofibers by replacing the hydroxyl groups.

[0102] By appropriately replacing the aqueous dispersion of cellulose nanofibers with an organic solvent, it is possible to prepare a cellulose nanofiber dispersion solution that is easily dispersed and compatible with resins and varnishes.Furthermore, by appropriately using a catalyst on the cellulose nanofibers, it is possible to replace the hydroxyl groups of the cellulose nanofibers with acid anhydrides or carboxylic acids to hydrophobize the cellulose nanofibers, thereby providing hydrophobic cellulose nanofibers dispersed in an organic solvent.

[0103] <Post-treatment of hydrophobic cellulose nanofibers> When the obtained hydrophobic cellulose nanofibers are in the form of a solution, they can be used as is without post-treatment, such as by forming them into a film or mixing them into a resin solution. When purifying the simple substance through post-treatment, the solvent, catalyst, and remaining unreacted hydrophobic reaction products can be filtered by suction filtration to recover the simple substance on filter paper. In this case, the purity of the hydrophobic cellulose nanofibers can be improved by repeatedly washing with a general-purpose solvent. After filtration, the recovered hydrophobic cellulose nanofibers can be dried in a dryer at 60°C for 2 hours to remove the solvent used for washing.

[0104] <Evaluation of hydrophobicity of hydrophobic cellulose nanofibers by FT-IR analysis> The degree of hydrophobization of the hydrophobized cellulose nanofiber material obtained according to this embodiment can be evaluated using FT-IR analysis as follows. After the reaction is complete, the solution is separated from the hydrophobic cellulose nanofibers by filtration. At this time, by filtration while washing with any organic solvent with a boiling point of 80°C or less, the remaining carboxylic acid group-containing monomer in the solution, the catalyst, the base, and the solvent contained in the cellulose nanofibers can be transferred to the filtrate side. Since the presence or absence of carbonyl groups can be confirmed later by FT-IR analysis, it is preferable to use an organic solvent that does not contain carbonyl groups or ketone groups. Next, the solid cellulose nanofibers separated by filtration are transferred to a heat-resistant container and placed in a 60°C dryer for 1 hour to volatilize the solvent contained in the cellulose nanofibers. Without being bound by theory, in order to dry efficiently, it is preferable to transfer the cellulose nanofibers to a metal petri dish or the like and spread them thinly to increase the surface area. In addition, heating to 100°C or above or heating for 3 hours or more may cause the cellulose nanofibers to irreversibly aggregate. Finally, the dried cellulose nanofibers are analyzed using FT-IR analysis. At this time, the cellulose nanofibers before the hydrophobization reaction are also dried in the same manner as above, and the degree of hydrophobization is evaluated by comparison as follows. The evaluation criteria are shown in the examples below.

[0105] <Hydrophobic cellulose nanofiber> The hydrophobized cellulose nanofiber of this embodiment is characterized by being represented by the following general formula (III).

[0106] [ka] [In general formula (III), R 1 represents a divalent carbonyl-containing aliphatic group or a divalent carbonyl-containing aromatic group; R 2 represents a divalent aliphatic group or a divalent aromatic group, either of which may have a substituent. n represents an integer of 10 to 500,000.]

[0107] The hydrophobized cellulose nanofibers of this embodiment are obtained by the above-mentioned method for hydrophobizing cellulose nanofibers of this embodiment. It is presumed that the hydrophobized cellulose nanofibers have a higher degree of hydrophobization than the hydrophobized cellulose nanofibers obtained using TEMPO as a catalyst. This is because the hydrogen atoms of the primary hydroxyl groups of the cellulose molecules in the hydrophobized cellulose nanofibers of this embodiment are replaced with carbonyl group-containing monomer residues or carboxylic acid group-containing monomer residues, and the carbonyl group-containing monomer residues or carboxylic acid group-containing monomer residues are bonded via methylene groups and oxygen atoms, resulting in a bulky structure. Therefore, the steric hindrance that occurs between the cellulose nanofiber units can suppress the hydrogen bonding and aggregation action via the hydroxyl groups. In contrast, the hydrophobized cellulose nanofibers obtained using TEMPO as a catalyst are inferior in bulkiness because the carboxyl groups are directly bonded to the carbon atoms that constitute the six-membered rings of the cellulose molecules, and it is presumed that the hydrophobized cellulose nanofibers of this embodiment have inferior heat resistance due to the presence of amide groups. In addition, the hydrophobized cellulose nanofibers of this embodiment have excellent adhesion to resins due to their high polarity.

[0108] Furthermore, the hydrophobized cellulose nanofiber of this embodiment is represented by the above general formula (III), R 1 and R 2 Because there is such a wide variety of types, there are many structural variations.

[0109] In the general formula (III), R 1 is R in general formula (II) 1 Therefore, R in the above general formula (II) is a divalent group derived from an aliphatic or aromatic carboxylic acid group. 1 It is a group missing a hydroxyl group (OH).

[0110] In the general formula (III), R 2Examples of the alkylene group include an alkylene group having 1 to 50 carbon atoms, which may be branched or cyclic, and a phenylene group having 6 to 12 carbon atoms. When the alkylene group or the phenylene group has a substituent, examples of the substituent include a monoamino group and a diamino group.

[0111] Other features of the hydrophobized cellulose nanofibers of this embodiment have been described in the above-mentioned method for hydrophobizing cellulose nanofibers, so description thereof will be omitted here.

[0112] The hydrophobized cellulose nanofiber of this embodiment can be added to an adhesive film for semiconductors. By adding the hydrophobized cellulose nanofiber to an adhesive film for semiconductors, it tends to be possible to reduce the coefficient of linear expansion (CTE) and increase the thixotropy. EXAMPLES

[0113] The present embodiment will be described in more detail below with reference to examples, but the present embodiment is not limited to the following examples. In the following, "parts" such as "0.04 parts of succinic anhydride" refer to "parts by mass".

[0114] [Example 1] The substance constituting the general formula (I) of the cellulose nanofiber was adjusted to a non-volatile content of 1 mass% using dimethyl sulfoxide (hereinafter referred to as "DMSO") as a solvent according to the method shown in "Solvent replacement of cellulose nanofiber aqueous dispersion" above, and the non-volatile content was distilled (dehydrated) and dispersed in the solvent to obtain a cellulose raw material liquid. 10 g of the cellulose raw material liquid was placed in a 100 mL separable flask, to which 0.04 parts of succinic anhydride, 0.001 parts of 4-dimethylaminopyridine (DMAP), and 0.5 parts of pyridine were added relative to the cellulose raw material liquid, and the separable flask was then closed to obtain a reaction system. The reaction liquid was stirred at room temperature for 24 hours at 250 rpm to obtain an intermediate of hydrophobic cellulose nanofiber in which an aliphatic carboxylic acid derived from succinic anhydride had been substituted (R in the general formula (II) above). 1Then, 0.03 parts of ethylenediamine and 0.001 parts of N,N-dicyclohexylcarbodiimide were added to the solution, and the mixture was stirred at 250 rpm at room temperature for 4 hours to obtain a hydrophobic cellulose nanofiber in which the amide groups were hydrophobized (R in the above general formula (III)). 2 =-C2H4-) was obtained.

[0115] [Example 2] In the same manner as in Example 1, the cellulose raw material liquid, succinic anhydride, DMAP, and pyridine were added to a 100 mL separable flask, and the intermediate (R 1 Then, 0.03 parts of phenylenediamine and 0.001 parts of N,N-dicyclohexylcarbodiimide were added to the solution, and the mixture was stirred at 250 rpm at room temperature for 4 hours to obtain a hydrophobic cellulose nanofiber in which the amide groups were hydrophobized (R in the above general formula (III) 2 =-C6H4-) was obtained.

[0116] [Example 3] In the same manner as in Example 1, 10 g of the cellulose raw material liquid, succinic anhydride, DMAP, and pyridine were added to a 100 mL separable flask, and the intermediate (R 1 Then, 0.03 parts of norbornanediamine and 0.001 parts of N,N-dicyclohexylcarbodiimide were added to the solution, and the mixture was stirred at 250 rpm at room temperature for 4 hours to obtain a hydrophobic cellulose nanofiber in which the amide groups were hydrophobized (R in the above general formula (III) 2 =-CH2NBCH2- (NB represents a norbornene skeleton) was obtained.

[0117] [Example 4] In the same manner as in Example 1, 10 g of the cellulose raw material liquid, succinic anhydride, DMAP, and pyridine were added to a 100 mL separable flask, and the intermediate (R 1Then, 0.03 parts of phenylene ether diamine and 0.001 parts of N,N-dicyclohexylcarbodiimide were added to the solution, and the mixture was stirred at 250 rpm at room temperature for 4 hours to obtain a hydrophobic cellulose nanofiber in which the amide groups were hydrophobized (R in general formula (III) 2 =-C6H4OC6H4-) was obtained.

[0118] [Example 5] In the same manner as in Example 1, 10 g of the cellulose raw material liquid, succinic anhydride, DMAP, and pyridine were added to a 100 mL separable flask, and the intermediate (R 1 Then, 0.03 parts of benzyldiamine and 0.001 parts of N,N-dicyclohexylcarbodiimide were added to the solution, and the mixture was stirred at 250 rpm at room temperature for 4 hours to obtain a hydrophobic cellulose nanofiber in which the amide groups were hydrophobized (R in general formula (III) 2 =-CH2C6H4-) was obtained.

[0119] [Example 6] In the same manner as in Example 1, 10 g of the cellulose raw material liquid, phthalic anhydride, DMAP, and pyridine were added to a 100 mL separable flask, and the intermediate (R 1 Then, 0.03 parts of ethylenediamine and 0.001 parts of N,N-dicyclohexylcarbodiimide were added to the solution, and the mixture was stirred at 250 rpm at room temperature for 4 hours to obtain a hydrophobic cellulose nanofiber in which the amide groups were hydrophobized (R in general formula (III) 2 =-C2H4-) was obtained.

[0120] [Comparative Example 1] The substance constituting the general formula (I) of the cellulose nanofiber was adjusted to a non-volatile content of 1 mass% using DMSO as the solvent according to the method described above in "Solvent replacement of cellulose nanofiber aqueous dispersion," and then distilled (dehydrated) and dispersed in the solvent to obtain the cellulose raw material liquid (I).

[0121] [Comparative Example 2] The substance constituting the general formula (I) of the cellulose nanofiber was adjusted to a non-volatile ratio of 1 mass% using the solvent DMSO according to the method shown in the above "Solvent replacement of cellulose nanofiber aqueous dispersion", distilled (dehydrated), and dispersed in the solvent to obtain a cellulose raw material liquid. 10 g of the cellulose raw material liquid was placed in a 100 mL separable flask, to which 0.04 parts of succinic anhydride, 0.001 parts of 4-dimethylaminopyridine (DMAP), and 0.5 parts of pyridine were added relative to the cellulose raw material liquid, and the separable flask was then closed with a lid to obtain a reaction system. The reaction liquid was stirred at room temperature for 24 hours at 250 rpm to obtain hydrophobic cellulose nanofibers in which aliphatic carboxylic acids derived from succinic anhydride had been substituted (R in general formula (II) 1 =-C2H4COOH) was obtained.

[0122] [Comparative Example 3] The substance constituting the general formula (I) of the cellulose nanofiber was adjusted to a non-volatile ratio of 1 mass% using the solvent DMSO according to the method shown in the above "Solvent replacement of cellulose nanofiber aqueous dispersion", distilled (dehydrated), and dispersed in the solvent to obtain a cellulose raw material liquid. 10 g of the cellulose raw material liquid was placed in a 100 mL separable flask, to which 0.04 parts of phthalic anhydride, 0.001 parts of 4-dimethylaminopyridine (DMAP), and 0.5 parts of pyridine were added relative to the cellulose raw material liquid, and the separable flask was then closed with a lid to obtain a reaction system. The reaction liquid was stirred at room temperature for 24 hours at 250 rpm to obtain hydrophobic cellulose nanofibers in which aromatic carboxylic acids derived from phthalic anhydride had been substituted (R in general formula (II) 1 =-C6H4COOH) was obtained.

[0123] <Evaluation> 1. Fiber diameter The fiber diameter of the hydrophobic cellulose nanofibers obtained in each of the Examples and Comparative Examples was measured according to the above-mentioned "Method for Analyzing Fiber Diameter of Hydrophobic Cellulose Nanofibers." The measurement results are shown in Tables 1 and 2.

[0124] 2.Resin dispersibility The hydrophobized cellulose nanofibers obtained in each Example and Comparative Example were added to an aliphatic acrylic resin and a bisphenol A type epoxy resin at 1% by mass, and evaluated according to the following evaluation criteria. The evaluation results are shown in Tables 1 and 2. Without being bound by theory, it is known that cellulose nanofibers are incompatible with other resin solutions and aggregate without exhibiting dispersibility because the numerous hydroxyl groups present in the molecules form hydrogen bonds with each other. [Evaluation Criteria] 〇: Good dispersibility When it is compatible with both aliphatic acrylic resins and bisphenol A type epoxy resins, and no aggregation or precipitation is observed. ×: Poor dispersibility If aggregation or precipitation is observed in either aliphatic acrylic resin or bisphenol A type epoxy resin. Without being bound by theory, if a material exhibits dispersibility in both aliphatic acrylic resin, which has a relatively low polarity among resins, and bisphenol A type epoxy resin, which has a relatively high polarity among resins, it can be expected that the material will also exhibit dispersibility in other resins.

[0125] 3. Hue The hue of the dispersion of hydrophobized cellulose nanofibers obtained in each Example and Comparative Example was judged by visual inspection. If the color was the same white color as after the solvent replacement before the hydrophobization reaction, it was rated as "white," and if it was black, it was rated as "black." The results are shown in Tables 1 and 2. If the hydrophobic structure deteriorates (decomposes), the material may turn yellow or black. Also, if the cellulose skeleton deteriorates (decomposes) due to the materials added during the hydrophobic reaction, the material may turn yellow or black. Therefore, a white color is preferable.

[0126] 4. Hydrophobicity In each of the Examples and Comparative Examples, after the reaction was completed, the solution and the hydrophobized cellulose nanofibers were separated by filtration. The solid hydrophobized cellulose nanofibers separated by filtration were transferred to a heat-resistant container and placed in a dryer heated to 60°C for 1 hour to volatilize the solvent contained in the hydrophobized cellulose nanofibers. The dried hydrophobized cellulose nanofibers were then analyzed using FT-IR analysis. At this time, the cellulose nanofibers before the hydrophobization reaction were also dried in the same manner as above, and the degree of hydrophobization was evaluated by comparison as follows. The evaluation results are shown in Tables 1 and 2. Note that for Examples 1, 2, and 6 and Comparative Examples 1 and 2, the infrared absorption spectra obtained by FT-IR analysis are shown in Figures 1 to 5, respectively. [Evaluation Criteria] 〇:3500cm -1 The peak area of ​​the hydroxyl group stretching before and after the reaction is reduced compared to before the reaction, and the peak area of ​​the hydroxyl group stretching before and after the reaction is reduced compared to before the reaction. -1 The peak area ratio of the carbonyl stretching occurring before and after reached more than 1% compared with the total area ratio. △:3500cm -1 The peak areas of the hydroxyl group stretching before and after the reaction did not change compared to before the reaction, but the peak areas of the hydroxyl group stretching -1 The peak area ratio of the carbonyl stretching occurring before and after reached more than 0.1% compared with the total area ratio. ×:3500cm -1 The peak area of ​​the hydroxyl group stretching before and after the reaction did not change compared to before and after the reaction, and the peak area of ​​the hydroxyl group stretching after the reaction did not change compared to before and after the reaction. -1 The peak area ratio of the carbonyl stretching occurring before and after was less than 0.1% compared to the total area ratio.

[0127] 5. Glass transition temperature (Tg) In each of the Examples and Comparative Examples, measurements were performed in a DSC differential scanning calorimeter (Rigaku Corporation Thermo Plus 7300) with carrier gas air (normal pressure), heating conditions: 30 to 300°C (initial temperature 30°C), heating rate 10°C / min, and sample weight: 3 mg packed into the DSC fan. The glass transition point of the hydrophobic cellulose nanofibers observed in response to heating was then measured. The measurement results are shown in Tables 1 and 2.

[0128] 6. Adhesion The hydrophobized cellulose nanofibers were dispersed in a DMSO solvent and mixed with 1% by mass of an acrylic polymer (Teisa Resin SG-708-6 or equivalent, manufactured by Nagase ChemteX), and the mixture was applied to a polypropylene film with a bar coater to form a 60 μm coating. The mixture was then dried at 120 ° C for 3 minutes to obtain a film. Similarly, a comparative sample was obtained by coating only the acrylic polymer without mixing the cellulose nanofibers to form a coating. Thereafter, when the coating was peeled off from the polypropylene film, if the peel strength was higher than that of the comparative sample, it was evaluated as having an adhesion improvement effect (◯), and if it was lower, it was evaluated as having no adhesion effect (×).

[0129] [Table 1]

[0130] [Table 2]

[0131] From Tables 1 and 2, it can be seen that Examples 1 to 6 have excellent dispersibility in resin and high hydrophobicity, heat resistance (Tg) and adhesion. Furthermore, none of Examples 1 to 6 used ingredients containing halogens or ionic substances in the raw materials, and the obtained hydrophobic cellulose nanofibers do not contain halogens or ionic substances. In contrast, Comparative Example 1, which used cellulose nanofibers that had not been hydrophobized, naturally had a low degree of hydrophobicity and was poor in dispersibility and adhesion to resin. Comparative Examples 2 and 3 differ from Examples 1 and 6, respectively, in that they were not amidated, but both had poor heat resistance.

Claims

1. A method for hydrophobizing cellulose nanofibers, comprising mixing and dispersing raw material components containing at least cellulose nanofibers, a carbonyl group-containing monomer or a carboxylic acid group-containing monomer, and a polar organic solvent in the same system, replacing the primary hydroxyl groups of the cellulose molecules constituting the cellulose nanofibers with organic groups containing a carbonyl group, and then mixing and dispersing an amine to amidate the organic groups.

2. The method for hydrophobizing cellulose nanofibers according to claim 1, wherein the carbonyl group-containing monomer or the carboxylic acid group-containing monomer and the amine are present in an amount of 1 to 20 parts by mass per 100 parts by mass of the cellulose nanofibers and the polar organic solvent combined.

3. 3. The method for hydrophobizing cellulose nanofibers according to claim 1 or 2, wherein the carbonyl group-containing monomer or the carboxylic acid group-containing monomer is one selected from the group consisting of aliphatic ring-opened carboxylic acids, aliphatic acid anhydrides, aliphatic acid dianhydrides, aromatic acid anhydrides, aromatic acid dianhydrides, and bis-aromatic acid dianhydrides.

4. The method for hydrophobizing cellulose nanofibers according to claim 1 or 2, wherein the amine is one selected from the group consisting of aliphatic amines, aromatic amines, and ether amines.

5. The method for hydrophobizing cellulose nanofibers according to claim 1 or 2, wherein the raw material components further contain one catalyst selected from the group consisting of organic base catalysts, Bronsted acid catalysts, and metal catalysts.

6. The method for hydrophobizing cellulose nanofibers according to claim 5, wherein the one catalyst selected from the group consisting of organic base catalysts, Bronsted acid catalysts, and metal catalysts is present in an amount of 0.01 to 0.5 parts by mass per 100 parts by mass of the cellulose nanofibers and the polar organic solvent combined.

7. The method for hydrophobizing cellulose nanofibers according to claim 5 , wherein the organic base catalyst is a nitrogen-containing organic compound.

8. The method for hydrophobizing cellulose nanofibers according to claim 1 or 2, wherein the raw material components further contain a base.

9. The method for hydrophobizing cellulose nanofibers according to claim 8 , wherein the base is a nitrogen-containing organic compound.

10. The method for hydrophobizing cellulose nanofibers according to claim 1 or 2, wherein the cellulose nanofibers are a cellulose nanofiber solution obtained by solvent-substitution of an aqueous dispersion of cellulose nanofibers having a non-volatile content of 10% by mass or less with a polar organic solvent.

11. The method for hydrophobizing cellulose nanofibers according to claim 1 or 2, wherein the fiber diameter of the cellulose nanofibers is 1 to 1000 nm, and the fiber diameter of the hydrophobized cellulose nanofibers is 1 to 300 nm.

12. The method for hydrophobizing cellulose nanofibers according to claim 1 or 2, wherein the raw material components do not contain any halogen-containing substances, cation-containing substances, or anion-containing substances.

13. A hydrophobized cellulose nanofiber represented by the following general formula (III): 【Chemistry 1】 [In general formula (III), R 1 represents a divalent carbonyl-containing aliphatic group or a divalent carbonyl-containing aromatic group; R 2 represents a divalent aliphatic group or a divalent aromatic group, either of which may have a substituent; and n represents an integer of 10 to 500,000.

Citation Information

Patent Citations

  • Thermoplastic resin composition, molding, automobile component, and method for producing thermoplastic resin composition

    JP2019151782A

  • Resin composition and method for producing the same

    JP2022159126A

  • Method for recovery / reuse of n-oxyl compound

    WO2010116794A1

  • Modified cellulose fine fibers and method for producing same

    WO2017073700A1

  • Method for producing polyamide

    WO2018056459A1